Real-Time Capable Multi-Hop Media Access Control Protocol For Smart Home Environment - M.Shukeri, Nurulfaizal (2017)
The Wireless Sensor Network (WSN) is a technology that is now often highlighted and various studies have been done to apply in life such as environmental monitoring, security and military applications. These include the study of the Internet of Things (IoT) and Smart Home, where it is now gaining popularity in the research environment. Nevertheless, to apply WSN in the Smart Home Environment, WSN protocols need to support real-time characteristics. This protocol must also be capable of transmitting time-sensitive data such as audio and video at low bit rates through a multi-hop network where coverage can be expanded. Therefore, this thesis proposes TSMAC MAC protocol. The performance is made against CSMA protocol